Community Support in Fish Feed Pellet Production Using Maggot in Kualu Nenas Village (Technical Preparation) - Nofirza, Nofirza; Ismu Kusumanto; Harpito, Harpito; Anwardi, Anwardi; Misra Hartati (Lembaga Riset dan Inovasi Al-Matani, 2025)
The condition during pandemic generally has significant impact to all the aspect in society. This condition is also occurring in Desa Kualu Nenas, that most of the people activities are as farmers and fish breeders. The high cost of fish feed is one of the main problems faced by almost all fish farmers. This community service aims to plan and prepare the need of a comprehensive solution, started from maggot cultivation, practice/workshop, and outreach to the community. It was carried out with all the limited conditions and try to utilizing the existing local resources. Maggot cultivation itself can be a new business opportunity for the community, with an ease of manufacture, cultivation process and the large number of market demands. For pellet ingredients, it is using a semi-automatic pelletizing machine has also been produced which has succeeded in making pellets, although it is still in progress of developing to make it more optimal. The results of the service raise hope from the community who want that this empowerment activity can be carried out sustainably in the form of assistance. Community Support in Fish Feed Pellet Production Using Maggot in Kualu Nenas Village (Technical Preparation)